(untitled) (Economics and region, 2019)
The article deals with the theoretical aspect of social responsibility of business, discusses the origins of the concept of social responsibility by analyzing classical and modern scientific research and schools, and provides the structure and definitions of this notion. The authors present the factors that influence the increasing significance that social responsibility of business has in society, and the problems of Georgian and Ukrainian business on its way to socially responsible behavior.